Perlindungan Hukum Terhadap Jemaah Umrah - Mustolih Siradj (SALAM: Jurnal Sosial dan Budaya Syar-i, 2016)
In recent years, the news about Umrah is adorned with the phenomenon of howchaotic the Umrah system, fraud, pilgrims abandoned by the organizers in Indonesia,transit country or Saudi Arabia, lodging facilities, consumption, and tariff war betweentravel that are very unfair competition. In this situation, the pilgrims are the mostdisadvantaged people. The knowledge of the rights of Umrah pilgrims today is still lowconcern wich is very easy to be the object of exploitation of the organizers who onlyprioritize profit (profit oriented). Umrah is an important duty for Muslims because they arethe majority of the population in Indonesia. Because of the importance of pilgrims asconsumers, Umrah is given protection professionally and proportionally. DOI: 10.15408/sjsbs.v3i3.7859